2017
DOI: 10.1002/suco.201600222
|View full text |Cite
|
Sign up to set email alerts
|

Influence of polypropylene fibers on the flexural behavior of reinforced concrete slabs with different opening shapes and sizes

Abstract: Funding informationNone.The effect of polypropylene fibers (PF) on the flexural behavior of reinforced concrete one-way slabs with opening was investigated in this paper. The evaluated parameters included four different PF volume percentages (0, 0.3, 0.6, and 0.9%), with and without opening, two opening shapes (square and circular), and three opening sizes (100, 150, and 200 mm). Three groups of tested slabs were casted: without opening, with square opening, and circular opening, resulting in a total of 28 sla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(10 citation statements)
references
References 20 publications
2
8
0
Order By: Relevance
“…Likewise, the adding ratio of 0.50% polypropylene fibers showed slightly less than double the load capacity of specimens free from fibers. Enhancing the load capacity of concrete slab specimens containing fibers as presented in the current study agreed with numerous previous studies [37], [38], [39], [40], [41]. Therefore, the effect of fibers added to pervious concrete may be restricted or related by several factors, such as the random distribution of fibers within the concrete matrix.…”
Section: Figure 9 Maximum Deflection Diagram Of the Control Pp And Wr...supporting
confidence: 91%
“…Likewise, the adding ratio of 0.50% polypropylene fibers showed slightly less than double the load capacity of specimens free from fibers. Enhancing the load capacity of concrete slab specimens containing fibers as presented in the current study agreed with numerous previous studies [37], [38], [39], [40], [41]. Therefore, the effect of fibers added to pervious concrete may be restricted or related by several factors, such as the random distribution of fibers within the concrete matrix.…”
Section: Figure 9 Maximum Deflection Diagram Of the Control Pp And Wr...supporting
confidence: 91%
“…Simply supported one-way RC slabs of (1.10 × 0.50 × 0.07) m 3 dimensions for the length, width, and height, respectively, were constructed and tested by Al-Rousan [34], with the test conducted as illustrated in Figure 2. The investigated parameters included in the experiment are illustrated in Figure 3, where (f) stands for PF volume fraction, for which four percentages were used (0, 0.3, 0.6, and 0.9%).…”
Section: Experimental Work Reviewmentioning
confidence: 99%
“…It was revealed that major improvements were recorded in ductility, stress redistribution capacity, and post-cracking propagation. The flexural performance of one-way slabs strengthened when the PF of different percentages was studied (0, 0.3, 0.6, and 0.9) % with square and circular openings by Al-Rousan [34].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, punching shear failure can occur in a conical shape, which causes a slab to dramatically collapse progressively after the induced load is redistributed, and consequent overloading the various structural elements within the system [ 2 , 3 ]. Also, several factors influence the flexural performance of RC slabs, including structural element size, cement, aggregate, moisture level, and ambient environmental conditions [ [4] , [5] , [6] ].…”
Section: Introductionmentioning
confidence: 99%